Impact of Herpesvirus Detection via Metagenomic Next-Generation Sequencing in Patients with Lower Respiratory Tract Infections - Zhang H; Zhang X; Zheng Y; Gu X; Fu Z; Gai W; Wang H (Infection and Drug Resistance)
Huihui Zhang,1,* Xiaojing Zhang,2,* Yafeng Zheng,2,* Xiao Gu,1 Zhongming Fu,1 Wei Gai,2 Huaying Wang1 1Department of Respiratory and Critical Care Medicine, The Affiliated People’s Hospital of Ningbo University, Yinzhou People’s Hospital, Ningbo, Zhejiang, 315040, People’s Republic of China; 2WillingMed Technology (Beijing) Co., Ltd, Beijing, People’s Republic of China*These authors contributed equally to this workCorrespondence: Wei Gai, WillingMed Technology (Beijing) Co., Ltd, No. 156 Jinghai 4th Road, Beijing Economic and Technological Development Zone, Beijing, 101103, People’s Republic of China, Email weigai@willingmed.com Huaying Wang, The Affiliated People’s Hospital of Ningbo University, Yinzhou People’s Hospital, No. 251, Baizhang East Road, Ningbo, 315040, People’s Republic of China, Email yingmeire@163.comPurpose: This study aimed to investigate the impact of herpesvirus detection by metagenomic next-generation sequencing (mNGS) of bronchoalveolar lavage fluid (BALF) on lower respiratory tract infections (LRTIs) patients’ lung microbiome composition and prognosis.Patients and methods: We initially enrolled 234 hospitalized patients with LRTIs who underwent BALF mNGS between February 2022 and May 2023. The study analyzed the clinical manifestations and the pulmonary microbial composition between herpesvirus detection (HD) and non-herpesvirus detection (non-HD) group.Results: After exclusions, a total of 201 patients were included, out of which 73 patients had herpesvirus detections (HD). The most frequently detected herpesviruses were Human herpesvirus 7 (HHV-7) (19.4%), Epstein-Barr virus (EBV) (12.4%), and cytomegalovirus (CMV) (10.4%). The HD group had a higher proportion of male patients (78.08% vs 55.04%, P = 0.001) and a greater incidence of hemoptysis and multilobar infiltrates compared non-HD group. Additionally, the HD group tended to have longer hospital stays compared to non-HD group, especially in immunosuppressed patients. Furthermore, in immunocompetent patients, there were significant differences in α diversity and β diversity between the HD group and non-HD group, but such differences were not observed in immunosuppressed patients.Conclusion: The presence of herpesvirus in patients with non-critical LRTI is associated with longer hospital stays and alterations in the lung’s microbial composition. Additionally, the impacts of herpesvirus presence are influenced by the immune status of the patients.Keywords: lower respiratory tract infections, herpesvirus detection, bronchoalveolar lavage fluid, microbial composition, mNGS